Genetic diversity and selection criteria of MPOB-Senegal oil palm (Elaeis guineensis Jacq.) germplasm by quantitative traits - Myint, Khin Aye; Amiruddin, Mohd Din; Rafii, Mohd Y.; Abd Samad, Mohd Yusoff; Ramlee, Shairul Izan; Yaakub, Zulkifli; Oladosu, Yusuff (Elsevier, 2019)
Understanding genetic structure of different vegetative, yield and yield component traits play a major role in oil palm breeding program. Based on this background, this study was carried out to evaluate the genetic diversity and heritability among 26 families of MPOB-Senegal oil palm germplasm using multivariate analysis to identify superior palms for future oil palm breeding program. To achieve this objective, data on yield components, bunch quality and vegetative traits were collected for eight consecutive years. The analysis of variance showed a significant variability among the families for most of the traits evaluated. The mean nut weight and rachis length showed high broad sense heritability value of 62.15% and 61.06% while the rest of the traits ranged from moderate to low. The evaluated families were grouped into six major clusters at the coefficient of 0.72 based on morphological traits with the aid of unweighted pair group method with arithmetic mean (UPGMA) dendrogram. This findings revealed that MPOB-Senegal germplasm exhibited important economic traits which are vital in oil palm improvement programs. Based on the results, the three families SEN02.05, SEN05.02 and SEN06.01 were identified as prospective families for high kernel content which could be the most essential sources of lauric acids for oleochemical industry. The information obtained from this study would be more useful if integrated with molecular study to have a comprehensive genetic variation pattern of MPOB-Senegal oil palm germplasm which could then be utilized in the development of core collection to preserve the widest genetic diversity with minimum family.